Genetic diversity and demographic history of wild yak (Bos grunniens mutus) inferred from mtDNA D-loop sequences - Zhijie, Ma; Jincheng, Zhong; Jintao, Xu; Wenlin, Bai; Jiye, Li; Dongzhi, Cairang; Xinyan, Jin; Jun, Zhang; Han Jianlin (2010)
The wild yak (Bos grunniens mutus) is considered as one of the endangered species. To provide useful information for conservation and utilization of this species, we investigated the genetic diversity and demographic history of wild yak by analyzing a 637 bp hypervariable fragment of 21 mitochondrial DNA (mtDNA) D-loop sequences including six sequenced in this study and 15 downloaded from GenBank. Forty-five variable sites and 15 haplotypes (including three haplotypes present firstly in this study) were identified, and the nucleotide and haplotype diversities were 0.024430 ± 0.012685 and 0.9619 ± 0.0260, respectively, indicating a rich genetic diversity in wild yak. The NJ phylogenetic tree revealed two distinct lineages and the selective neutrality and mismatch distribution tests all showed no population expansion event in the demographic history of the wild yak.